Amoniasi Daun Kelapa Sawit Dengan Beberapa Taraf Urea Dan Pengaruhnya Terhadap Kandungan Gizi Dan Kecernaan Secara In Vitro - Mardiati Zain; Erpomen Erpomen; Kartini Kartini (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2007)
An experiment was conducted to evaluate the efect of ammoniation on the digestibility of oil palm frond. As treatments, oil palm frond was mixed with difference levels of urea of 0, 3, 6 and 9 % of DM basis. The mixtures were then added 15 % dried chicken manure and the incubated in anaerobic condition for one week. Parameters measured included: fiber fractions content and digestibility of DM and OM. Data were statistically analyed by variance analysis in a block randomized design. Results showed that the treatments gave significant efect on the digestibility. Digestibility of DM and OM of oil palm frond treated with 6 and 9 % urea were higher than that of treated with 0 and 3 % of urea. The best digestibility was found by ammoniation with 6 % urea.